Efektivitas Penggunaan Media Gambar Terhadap Keterampilan Menulis Puisi Pada Siswa Kelas V SD Negeri 108422 Perbaungan - Rospita Harahap, Sujarwo (Pusdikra Publishing, 2022)
The process of applying pictorial word cards to improve poetry writing skills for fifth graders at SD Negeri 108422 Perbaungan was carried out in two cycles. Students' poetry writing skills in cycle I such as cycle II have increased. Weaknesses in cycle I, such as students having difficulty writing poetry, students having difficulty distinguishing between writing poetry and writing sentences, and teachers who are less able to condition the class to be conducive can be corrected in cycle II. In cycle II the teacher uses a loud voice and goes around the class to condition learning activities to be conducive, the teacher explains in more detail and gives examples of the differences between writing poetry and writing stories, as well as giving appreciation and motivation to students to be more enthusiastic in writing poetry well. After corrective action was taken in cycle II, students were able to write poetry properly and correctly. This can be proven by improving students' poetry writing skills from cycle I to cycle II. The effectiveness of the use of picture media on poetry writing skills in fifth grade students of SD Negeri 108422 Perbaungan after being applied to picture word cards is known from the comparison of students' poetry writing scores from the pre-cycle. Cycle I and Cycle II At the pre-cycle stage, students who scored 70 were 23 students with a percentage of 60.53%. The poetry writing skills of the first cycle students experienced an increase, namely students who completed with a score of 70 as many as 27 students with a percentage of 71.05%. Cycle II also experienced an increase in students who completed with a score of 70 as many as 32 students with a percentage of 84.21%.